Study of Fatigue Behavior of Epoxy‐Carbon Composites under Mixed Mode I/II Loading. Issue 2 (18th October 2017) - Rocandio, Clara; Viña, Jaime; Argüelles, Antonio; Rubiera, Silvia
Abstract : This paper presents an experimental assessment of the initiation and propagation of interlaminar cracks under mixed mode I/II dynamic fracture loading of a composite material with an MTM45‐1 epoxy matrix and unidirectional IM7 carbon‐fiber reinforcement. The aims of the experimental program developed for this purpose are to determine, on the one hand, the initiation curves of the fatigue delamination process, understood as the number of load cycles needed to generate a fatigue crack, and on the other, the crack growth rate (delamination rate) for different percentages of static Gc, in both cases for two mode mixities (0.2 and 0.4) and for a tensile ratio R = 0.1. All this with the goal of quantifying the influence of the degree of mode mixity on the overall behavior of the laminate under fatigue loading. The results show that the energy release rate increases with increasing loading levels for both degrees of mode mixity and that the fatigue limit is located around the same percentages. However, crack growth rate behavior differs from one degree of mode mixity to the other. This difference in the behavior of the material may be due to the varying influence of mode I loading on the delamination process. Abstract : The initiation curves of the fatigue delamination process of a composite materials with an MTM45‐1 epoxy matrix and unidirectional IM7 carbon‐fiber reinforcements have been obtained for two mode mixities and for a tensile ratio. Crack growth rate behavior differs from one degree of mode mixity to the other, being the cause the varying of mode I loading on the delamination process.